Penerapan Model Pembelajaran Problem Based Learning Untuk Mengembangkan Kemampuan Berpikir Kritis Anak Usia 5-6 Tahun - Winda Novia Windaryati (Universitas Muhammadiyah Surakarta, 2026)
Early childhood learning involves children as the center of learning and meaningful and enjoyable activities. However, there are problems that there are still some who have not implemented problem-based learning models, there are still many learning that are not child-centered, and limited facilities and teacher skills in creating learning media that are in accordance with the times. This study aims to determine the application of the Problem Based Learning (PBL) learning model in developing critical thinking skills of children aged 5-6 years at Pembina Boyolali State Kindergarten in the 2024/2025 Academic Year. This study uses a descriptive qualitative approach with the research location at Pembina Boyolali State Kindergarten and the research subjects are class B3 teachers. Data collection techniques are carried out through observation, interviews, documentation. Data analysis is carried out through the process of data condensation (Condentation), Data Presentation (Display Data), Drawing Conclusions / Verification. The results of the study show that the application of the Problem Based Learning model is carried out systematically through 5 stages, namely (1) Orientation of students, (2) Organizing students, (3) Guiding individual and group investigations, (4) Developing and presenting work results, (5) Analyzing and evaluating the problem-solving process. This model encourages children's active involvement in the critical thinking process, such as finding problems, putting forward ideas, formulating solutions, and linking learning to real experiences. As in the process of flood simulation activities, children become sensitive to the relationship between garbage and floods, and apply positive behavior in disposing of garbage in its place. The application of Problem Based Learning significantly supports the development of 21st century skills, especially critical thinking